Exploring the Synergistic Effects of Heavy Metal contaminants on Aquatic Organisms - Shabnam Khan; Ritu Raj Singh; Astha Priyadarshini; Rajesh Kumar (International Journal of Marine Life, 2024)
Human activities have a profound effect on aquatic habitats by altering water and sediment quality, which in turn impacts resident organisms. These changes are primarily caused by pollutants from agricultural, industrial, and health-related sources. Industrial effluents, often containing hazardous heavy metals such as chromium, manganese, and lead, are a major source of environmental toxicity. The discharge of these pollutants makes water unsafe for drinking, irrigation, and industrial uses, necessitating effective management strategies to safeguard environmental health and biodiversity. Heavy metal contamination originates from various sources, including industrial processes like leather tanning, chrome plating, and battery manufacturing. Agricultural runoff, carrying fertilizers and pesticides, and thermal pollution from power plants also contribute significantly to this issue. Additionally, the rapid growth of the electronics industry and the resultant e-waste exacerbate heavy metal pollution in water bodies. The consequences of heavy metal pollution on aquatic environments are severe. While metals like iron, copper, and zinc are essential for cellular functions, others like lead can be toxic even in small amounts. The increasing levels of heavy metal contamination, particularly in areas such as China, highlight the urgent need for developing sustainable and cost-effective methods for removing these pollutants from water. Addressing this issue is crucial for reducing its negative impact on ecosystems and ensuring the health of both aquatic life and human populations. Moreover, implementing stricter regulations on industrial discharge, promoting eco-friendly agricultural practices, and enhancing public awareness about the sources and impacts of heavy metal pollution are essential steps toward mitigating this environmental challenge. Collaborative efforts between governments, industries, and communities will be key in creating a clean and safe aquatic environment for future generations.
Keywords: Agriculture; Heavy metal; Pollution; Power plant; aquatic organisms